2019
DOI: 10.3390/antiox8120620
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Atherosclerotic Effect of Hibiscus Leaf Polyphenols against Tumor Necrosis Factor-alpha-Induced Abnormal Vascular Smooth Muscle Cell Migration and Proliferation

Abstract: The proliferation and migration of vascular smooth muscle cells (VSMCs) are major events in the development of atherosclerosis following stimulation with proinflammatory cytokines, especially tumor necrosis factor-alpha (TNF-α). Plant-derived polyphenols have attracted considerable attention in the prevention of atherosclerosis. Hibiscus leaf has been showed to inhibit endothelial cell oxidative injury, low-density lipoprotein oxidation, and foam cell formation. In this study, we examined the anti-atherosclero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 40 publications
3
25
0
1
Order By: Relevance
“…The cyclin D1 gene, which is tightly correlated with cancerous cell proliferation, has been considered a marker molecule [ 36 ]. Similarly, cyclin E and CDK2/4/6 also play key roles in the G0/G1 transition in the cell cycle [ 37 40 ]. Furthermore, p21 and p27 act by binding CDK in the G1 phase of the cell cycle, leading to inhibition of the phosphorylation of other proteins such as retinoblastoma, which is necessary for cell cycle progression [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cyclin D1 gene, which is tightly correlated with cancerous cell proliferation, has been considered a marker molecule [ 36 ]. Similarly, cyclin E and CDK2/4/6 also play key roles in the G0/G1 transition in the cell cycle [ 37 40 ]. Furthermore, p21 and p27 act by binding CDK in the G1 phase of the cell cycle, leading to inhibition of the phosphorylation of other proteins such as retinoblastoma, which is necessary for cell cycle progression [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Administration of HS calyces extract significantly decreased the levels of different pro-inflammatory biomarkers such as TNF-α ( 9 , 11 , 16 , 31 , 40 – 43 ), Interleukin 6 (IL-6) ( 11 , 16 , 17 , 40 , 42 44 ), iNOS ( 31 , 45 ), Toll-like receptor 4 (TLR4) ( 16 ), Interleukin 1β (IL-1β) ( 9 , 16 , 42 ), MCP-1 ( 11 , 16 , 42 ), Ang I ( 46 ), Ang II ( 26 ), ACE1 ( 24 26 , 47 ), NF-κB ( 17 ), and Cyclooxygenase-2 (COX-2) ( 38 , 48 ). It also significantly decreased the levels of inflammatory manifestations of ear edema ( 1 , 49 ) and paw edema ( 11 ).…”
Section: Resultsmentioning
confidence: 99%
“…Other promoter and various factors could modify chemical components including soil, fertility, pH, temperature, humidity and other stresses ( Kandhare et al, 2012 , Da-Costa-Rocha et al, 2014 ). Previously Malinowski et al, 2019 , Chou et al, 2019 , reported that the EO production depends on the seasonal variation and various environmental factors. It also increases the common volatile compounds natures due to the stress condition.…”
Section: Resultsmentioning
confidence: 99%